The Influence of Indonesian Netizens' Response to the #Julidfisabilillah Movement on X (Twitter) in Fighting the Israel Defence Forces (IDF) - Nanda, Reyhan Alif; Sofianti, Christina Eka; Imawan, Khaerudin; Hermawan, Abdul Jalil (Indonesian Journal of Advanced Research, 2024)
The rapid development of today's technology, including the use of social media, especially X (Twitter) has become a common part of daily life regardless of the social class and age of the user. This study aims to analyze the influence of #JulidFiSabilillah movements on platform X (Twitter), in the context of countering the actions of Israel Defence Forces (IDF). This study uses quantitative methods with a focus on statistical analysis and New Media theory to understand the response of Indonesia netizens to this movement. Data was collected through a survey of 400 respondents using non-probability sampling techniques. The results of the hypothesis test analysis using the t-test, obtained a t-calculation result of 36,007 (tcal>ttable 1,966) with a significance level of 0.004 (0.004<0.05), indicating that (H0) was rejected and (Ha) was accepted. The conclusion of this study shows that the #JulidFiSabilillah Movement has a significant influence on the Netizen Response Indonesia.